Prevalence of depression among women attending a primary urban care clinic in Malaysia. - Mohd Sidik, Sherina; Arroll, Bruce; Goodyear-Smith, Felicity; Ahmad, Rozali (Singapore Medical Association, 2012)

(untitled)
Depression affects more women than men in Malaysia. The objective of this paper was to determine the prevalence of depression and its associated factors among women attending a government primary care clinic. MeThODs A cross-sectional study was conducted in a government-funded primary care clinic in Malaysia. Consecutive adult female patients attending the clinic during the data collection period were invited to participate. The participants completed self-administered questionnaires (including the validated Patient Health Questionnaire [PHQ-9], which was translated into the Malay language). ResUlTs A total of 895 female patients participated in the study (response rate 87.5%). The prevalence of depression (PHQ-9 scores ≥ 10) was 12.1%. Based on multiple logistic regression analysis, certain stressful life events were found to be associated with depression (p < 0.05). These factors, arranged from highest to lowest risk, were financial problems (odds ratio [OR] 3.7, 95% confidence interval [CI] 2.2-6.2), unhappiness in the parent-child relationship (OR 3.0, 95% CI 1.2-7.5), history of serious illness (OR 2.4, 95% CI 1.1-5.2), unhappiness in family relationships (OR 2.3, 95% CI 1.1-4.7) and unhappiness at work (OR 2.2, 95% CI 1.1-4.3) (p < 0.05). CONClUsION The prevalence of depression among participants in this study was clinically significant and corresponded with the findings of other international studies. Factors associated with depression need to be highlighted and addressed accordingly. Clinicians in Malaysia should be aware of this prevalence when making diagnoses in primary care.